Characterization of Brazilian floral honey produced in the states of Santa Catarina and São Paulo through ultraviolet–visible (UV–vis), near-infrared (NIR), and nuclear magnetic resonance (NMR) spectroscopy - Nunes, Aline; Zilto Azevedo, Gadiel; Rocha dos Santos, Beatriz; Vanz Borges, Cristine [UNESP]; Pace Pereira Lima, Giuseppina [UNESP]; Conte Crocoli, Luana; Moura, Sidnei; Maraschin, Marcelo (Elsevier, 2022)
Honey is considered a complex matrix for presenting a range of secondary metabolites originating from the regional flora. It has been highlighted as a functional food consumed worldwide and frequently suffering from adulteration. Fraud methods have been sophisticated over the years, indicating the need of a continuous updating of the existing analysis methods. For this reason, analytical techniques applied to honey have been expanded, allowing the detection of fraud and the determination of geographic and botanical origin, to guarantee the authenticity of the product. In this sense, this study aimed to characterize floral honey samples in 2019–2020 and 2020–2021 harvests in the states of Santa Catarina (SC, southern Brazil – n = 73) and São Paulo (SP, southeastern Brazil – n = 59), through UV–vis, NIR, and NMR spectroscopies. The total reduced capacity showed a wide variation (0.76–12.8 mg GAE.g−1) among the SC and SP samples. Spectroscopic analyses through UV–vis and NMR with the application of PCA proved effective for discriminating honey samples according to their geographical origin. The honey UV–vis spectral profiles allowed to detect wavelengths that can be associated with honey adulteration, however further studies are needed to establish the accuracy of detection regarding fraud. In summary, a set of analytical protocols is presented to determine the geographical origin of floral honey, even when originated from regions with great biodiversity such as Brazil.
Keywords: Chemometrics; Honey; Metabolomics; PCA; Spectral profile; Total phenolics; Typification